The Influence of Change Load Against Fuel Cost in Coal-fired Power Tarahan Lampung Unit 3 and 4 - Endah Komalasari; Rahmattulloh Rahmattulloh; Herri Gusmedi (Universitas Lampung, 2017)
Abstract—The operation of a power plant depends on fuel where fuel costs are incurred on a generating unit is a function of the plant load. The ability power plant carry the load determine the reliability of an electrical system, hence the power raised always be done equal to needs in side load all the time. Fluctuations demand of electrical power in side load will cause fluctuations change fuel cost. In this paper, the correlation both commonly called input-output characteristics of the power plant needs to be determined. These characteristics declared total input tons of coal per hour is used and net electrical output where the output power is available to the electric utility. One way to achieve this goal is to match polynomial regression on the data using a second order polynomial. This model allows the study of the incremental fuel cost resulting from a change load in a coal-fired power plant.Keywords—Coal-fired power, economic dispatch, incremental cost characteristics, input-output characteristics, second order polynomial regression.